Family Medicinal Plant Cultivation (TOGA) in the New Normal of the Covid-19 Pandemic - Hanifah Ikhsani; Ervayenri; Azwin (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
The existence of Covid-19 quickly resulted in many losses, so the government implemented a new normal. This policy encourages all parties to take various ways to restore the economic, social, and cultural conditions, one of which is by cultivating Family Medicinal Plants (TOGA) which also functions to increase the body immunity and utilizing yard land that has not been managed optimally. The activities are socialization about TOGA, cultivation techniques, cultivation practices, mentoring, and evaluation. This activity was carried out during the new normal at RT.03 RW. 05, Limbungan Rumbai was attended by 15 partners. Partners are enthusiastic about cultivating TOGA and have increased knowledge after the implementation of the extension. The practice of planting the 45 TOGA seeds given, 100% succeeded in growing well. The success of growing seedlings include quality seeds, correct planting techniques and giving fertilizer at the right dose.